Association of Wrist Ratio, Body Mass Index, and Hand Grip Strength with Boston Carpal Tunnel Questionnaire Scores among Online Motorcycle Drivers - Rulan Adnindya; Syarinta Adenina; Tri Suciati (Majalah Kesehatan Indonesia, 2026)
Carpal tunnel syndrome (CTS) is a common work-related musculoskeletal disorder associated with repetitive hand activities. Online motorcycle drivers are at increased risk due to prolonged gripping and repetitive wrist movements. Anthropometric factors and hand strength have been suggested as potential contributors to CTS, but evidence remains inconsistent, particularly in informal occupational groups. This study aimed to analyze the association between wrist ratio, body mass index (BMI), and hand grip strength with CTS symptoms based on the Boston Carpal Tunnel Questionnaire (BCTQ). An observational cross-sectional study was conducted involving 80 online motorcycle drivers selected using consecutive sampling. Wrist ratio, BMI, and hand grip strength were measured, while CTS symptoms were assessed using the BCTQ. Data was analyzed using univariate and bivariate statistical tests. CTS symptoms were identified in 48.8% of participants. A substantial proportion of participants were classified as overweight or obese (approximately 44%). Statistical analysis showed no significant association between wrist ratio, BMI, or hand grip strength and CTS symptoms (p > 0.05). Wrist ratio, BMI, and hand grip strength were not significantly associated with CTS symptoms among online motorcycle drivers. These findings suggest that CTS is a multifactorial condition influenced by factors beyond basic anthropometric and strength measurements.